Transcriptomics of Listeria monocytogenes Treated With Olive Leaf Extract - Liu, Yanhong; Fang, Ting; Suo, Yujuan; Gao, Shigang; Baranzoni, Gian Marco; Armstrong, Cheryl M. (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a regulated foodborne pathogen that is known to cause listeriosis, a disease associated with high mortality rates in human. Olive leaf extract (OLE) has been shown to act as a plant antimicrobial and inhibit the growth of pathogens such as L. monocytogenes although its mode of action has not been defined. To help identify the cellular mechanisms important for conveying these beneficial traits, RNA-Seq was used to study the transcriptome of L. monocytogenes upon exposure to a sub-lethal level of OLE. Results obtained from cells cultured both with and without OLE at two different time points (3.5-h and 24-h) revealed 661 genes that were differentially expressed. Of the differentially expressed genes (DEGs) identified, transcription was altered for 171 genes in response to the 3.5-h olive leaf extract treatments while 490 genes were altered in response to the 24-h OLE treatment. These DEGs included but were not limited to genes encoding for signal transduction, ATP-binding cassette (ABC) transporters, and the phosphotransferase system (PTS). Interestingly, several virulence-related genes were down-regulated including an ABC transporter permease previously shown to negatively regulate biofilm formation, genes involved in flagella assembly and binding/entry into host cells as well as those regulating acid resistance suggesting that olive leaf extract may decrease the virulence potential of L. monocytogenes. Furthermore, quantitative reverse-transcription PCR (qRT-PCR) was used to validate the data obtained via RNA-Seq. Our study provides insight into the mode of action of OLE treatment against L. monocytogenes and may aid in identifying synergetic strategies to inhibit L. monocytogenes in food.